THE CONCEPT AND COMPONENTS OF PROJECTIVE THINKING IN UZBEKISTAN’S EDUCATIONAL REFORMS - Kuchimova Farida Tashtemirovna (Web of Journals Publishing, 2025)
This study explores the theoretical foundations and structural components of projective thinking, emphasizing its role in contemporary education and future-oriented intellectual activity. Projective thinking is defined as the mental ability to anticipate, model, and strategically plan future events by synthesizing cognitive and non-cognitive factors [1,3]. The paper examines its philosophical roots, psychological mechanisms, and pedagogical applications, with particular attention to its relevance in the context of Uzbekistan’s educational reforms. The research adopts an IMRAD approach, integrating literature review, comparative analysis, and empirical insights. Findings indicate that projective thinking comprises interrelated components analytical-synthetic processes, prognostic reasoning, creative intuition, value orientation, and emotional regulation that together enable learners to effectively navigate uncertainty and innovate [4,7]. Recommendations are provided for integrating projective thinking development into curricula through interdisciplinary and project-based methodologies.
Keywords: Projective thinking, cognitive components, non-cognitive factors, future-oriented thinking, educational innovation, Uzbekistan.